Preparation method of amino acid ion intercalated MgFe-LDHs composite coating
By forming an amino acid ion intercalation MgFe-LDHs composite coating on the surface of the magnesium alloy, the problem of insufficient corrosion resistance of magnesium alloy is solved, and the high corrosion resistance and good biocompatibility of magnesium alloy in biomedical applications is achieved.
Patent Information
- Application Number
- CN202411683562.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-07
AI Technical Summary
The existing surface protection technology of magnesium alloys is difficult to effectively enhance the corrosion resistance of magnesium alloys, especially in biomedical applications, the corrosion resistance and biocompatibility of MgAl-LDH coatings are insufficient.
Using the preparation method of the MgFe-LDHs composite coating of amino acid ion intercalation, a PEO coating is formed by plasma electrolytic oxidation, and then FeOOH and amino acids are deposited on its surface, and an MgFe-LDH coating with the amino acids is formed by hydrothermal treatment.
It significantly enhances the corrosion resistance and biocompatibility of magnesium alloys. The products after coating corrosion are harmless to the human body, with good biocompatibility and bone repair effects.
Smart Images

Figure BDA0005148937560000101 
Figure HDA0005148937570000011 
Figure HDA0005148937570000012
Abstract
Description
1. Technical field:
[0001] The invention relates to the technical field of magnesium alloy surface protection treatment, and in particular to a method for preparing an amino acid ion intercalated MgFe-LDHs composite coating. 2. Background technology:
[0002] Magnesium alloys have the characteristics of light weight, elastic modulus close to bone, good biocompatibility, high specific strength and degradability. The degradation products of magnesium alloys are Mg 2+ , H 2 and Mg(OH) 2 ,Mg 2+ It can promote apoptosis of tumor cells and participate in human metabolism, promoting osteogenic differentiation. 2 Can remove free radicals, anti-inflammatory, Mg(OH) 2 It can create an alkaline environment to kill bacteria and regulate the tumor microenvironment. Therefore, magnesium alloys have received extensive attention in the biomedical field. However, its chemical properties are active, its corrosion rate is fast, and it produces excessive corrosion products, which can cause inflammation and other adverse effects in the human body. Therefore, how to enhance the corrosion resistance of magnesium alloys is a major problem in the application of magnesium alloys.
[0003] Surface modification technology is one of the important technologies for magnesium alloy corrosion protection, including chemical conversion treatment, anodic oxidation, plasma electrolytic oxidation (PEO), etc. However, the single coating prepared by these existing technologies cannot completely prevent corrosion. Therefore, it is urgent to develop a composite coating that can better enhance the corrosion resistance of magnesium alloys.
[0004] Layered double hydroxide (LDH), commonly known as hydrotalcite, is a layered material composed of positively charged layers and anions in the middle that balance the charge. Its anions have weak binding force with the layers and can be replaced. It can reduce the concentration of the corrosive solution and slow down the corrosion rate of the material by exchanging the anions between the interlayer anions and the anions of the solution. At present, the magnesium alloy LDH coating that is studied more is MgAl-LDH coating. Because the corrosion resistance of MgAl-LDH cannot meet the requirements, corrosion inhibitors are usually inserted into LDH or the LDH coating is modified. For example, the literature Zhang Jumei, Wu Jingwen, Li Jiacheng, et al. Transactions of the Indian Ceramic Society, 2024, 83(2): 126-33, Xu Dan, Zhuo Zhangzelong, Xie Zhihui, et al. Corrosion Science, 2024, 236: 1122229 and Han Xing, Wang Yongqin, Hu Jia, et al. Materials and Corrosion-Werkstoffe Und Korrosion, 2023, 74(5): 754-65 respectively introduce V 2 O 7 4- Insertion of LDH coating, mild treatment to obtain LDH coating and insertion of PO 4- , preparation method of superhydrophobic LDH coating and its effect on the corrosion resistance of magnesium alloy.
[0005] Since Al is neurotoxic and harmful to the human body, MgAl-LDH is difficult to be implanted in the human body. As Fe is an essential element for the human body, MgFe-LDH coating has attracted extensive attention in the medical application of magnesium alloys because it can enhance the corrosion resistance of magnesium alloys and enhance the biocompatibility of samples. However, its corrosion resistance and biocompatibility still cannot meet biological needs. 3. Summary of the invention:
[0006] The technical problem to be solved by the present invention is: according to the existing urgent need for better enhancing the corrosion resistance of magnesium alloy composite coatings and the technical problem that MgAl-LDH is difficult to be implanted in the human body, the present invention provides a method for preparing an amino acid ion intercalated MgFe-LDHs composite coating. The preparation method of the present invention is simple, convenient and environmentally friendly. The prepared coating does not harm human health after degradation and has good biocompatibility and strong corrosion resistance.
[0007] In order to solve the above problems, the technical solution adopted by the present invention is:
[0008] The present invention provides a method for preparing an amino acid ion intercalated MgFe-LDHs composite coating, the preparation method comprising the following steps:
[0009] 1) preparing a magnesium alloy matrix, and then pretreating the magnesium alloy matrix;
[0010] 2) Plasma electrolytic oxidation of PEO is performed on the pretreated magnesium alloy substrate to obtain a PEO sample, and the obtained PEO sample is placed in anhydrous ethanol for standby use;
[0011] 3) FeCl 2 ·4H 2 O, or amino acids and FeCl 2 ·4H 2 O is dissolved in deionized water to prepare solution A; the obtained solution A is placed in a container, and then the PEO sample obtained in step 2) is placed, and then the container is placed on a shaker at room temperature for shaking treatment;
[0012] 4) placing the sample obtained after the treatment in step 3) in anhydrous ethanol for ultrasonic washing, and then drying it in an oven;
[0013] 5) preparing a NaOH solution so that the pH of the NaOH solution is 9 to 11, and then adding amino acids;
[0014] Alternatively, a NaOH solution is prepared so that the pH of the NaOH solution is 9 to 11;
[0015] 6) placing the sample dried in step 4) and the solution prepared in step 5) in a polytetrafluoroethylene autoclave for heating treatment;
[0016] 7) The sample after the heat treatment in step 6) is ultrasonically cleaned with anhydrous ethanol, and then placed in an oven for drying (drying temperature is 40-60° C., and drying time is 12-48 hours), and after drying, an amino acid ion intercalated MgFe-LDHs composite coating is obtained.
[0017] According to the above-mentioned method for preparing the amino acid ion intercalated MgFe-LDHs composite coating, the magnesium alloy substrate in step 1) is a magnesium alloy rod with a diameter of 10 mm; when used, the magnesium alloy rod is cut into thin sheets with a thickness of 1 to 3.5 mm.
[0018] According to the above-mentioned method for preparing the amino acid ion intercalated MgFe-LDHs composite coating, the specific process of pretreating the magnesium alloy substrate in step 1) is as follows:
[0019] First, the front, back and sides of the magnesium alloy substrate are polished in turn with 400-mesh water-abrasive sandpaper, 800-mesh water-abrasive sandpaper and 1000-mesh water-abrasive sandpaper; the polished magnesium alloy substrate is placed in anhydrous ethanol for ultrasonic cleaning; after cleaning, the sample is taken out and placed back in anhydrous ethanol for standby use (by pre-treating the magnesium alloy substrate, the oxide film and impurities on the surface of the magnesium alloy can be removed to prepare a better coating).
[0020] According to the preparation method of the amino acid ion intercalated MgFe-LDHs composite coating, the specific process of the plasma electrolytic oxidation in step 2) is:
[0021] First, potassium hydroxide and sodium glycerophosphate are dissolved in deionized water to prepare a mixed solution, and the obtained mixed solution is used as an electrolyte and placed in a graphite electrode; a constant voltage method is used to adjust the frequency of the high-frequency pulse power supply to 900-1200 Hz, a duty cycle to 10%, a voltage to 300-380 V, and a boost time to 3-15 s; the sample obtained in step 2) is placed in the mixed solution, connected to the positive electrode of the power supply, the graphite electrode is connected to the negative electrode of the power supply, and the instrument is turned on for plasma electrolytic oxidation, and the timing is 2-5 minutes (the purpose of plasma electrolytic oxidation is to form a dense and porous MgO ceramic coating on the surface of the magnesium alloy, which can better perform chemical deposition to form the coating).
[0022] According to the above-mentioned method for preparing the amino acid ion intercalated MgFe-LDHs composite coating, the addition ratio of potassium hydroxide, sodium glycerophosphate and deionized water is 40-50g:30-50g:4L.
[0023] According to the above-mentioned preparation method of amino acid ion intercalated MgFe-LDHs composite coating, in step 3), FeCl 2 ·4H 2 When FeCl2O2 is dissolved in deionized water, 2 ·4H 2 The mass volume ratio of O and deionized water added is 1-5 mg:1 mL;
[0024] The amino acid and FeCl 2 ·4H 2 When FeCl2O2 is dissolved in deionized water, 2 ·4H 2 The ratio of O, amino acid and deionized water added is 1-5 mg: 0.2-1 mg: 1 mL.
[0025] According to the above-mentioned preparation method of the amino acid ion intercalated MgFe-LDHs composite coating, during the shaking treatment in step 3), the rotation speed of the shaking table is controlled to be 10 to 100 rpm and the shaking time is 60 to 120 min.
[0026] According to the above-mentioned preparation method of the amino acid ion intercalated MgFe-LDHs composite coating, during the drying in step 4), the drying temperature is controlled to be 40 to 60° C. and the drying time is controlled to be 12 to 48 hours.
[0027] According to the above-mentioned method for preparing the amino acid ion intercalated MgFe-LDHs composite coating, in step 5), the ratio of the amount of the amino acid to the amount of the NaOH solution added is 10-100 mg:75 mL.
[0028] According to the above-mentioned method for preparing the amino acid ion intercalated MgFe-LDHs composite coating, during the heating treatment in step 6), the temperature is controlled to be 80-150° C. and the heating time is 3-10 hours.
[0029] The positive beneficial effects of the present invention are:
[0030] 1. The technical solution of the present invention first prepares FeOOH and Fe-Tyr coatings by chemical deposition, and then obtains MgFe-LDH(Tyr) and MgFe(Tyr)-LDH coatings inserted with amino acids by hydrothermal treatment. The method of the present invention is simple, convenient, easy to operate, environmentally friendly, and low in cost.
[0031] 2. The coatings prepared by the method of the present invention are dense and uniform in thickness. Both coatings grow uniformly and densely on the magnesium alloy substrate. They present a vertically growing nanosheet structure. The loaded amino acids have a strong ability to replace negative ions in the corrosive solution (such as Cl - ), thereby enhancing the corrosion resistance of magnesium alloys. The corrosion current density of bare magnesium is 1.18×10 (-5) A.cm -2 The corrosion current densities of MgFe-LDH(Tyr), MgFe(Tyr)-LDH, MgFe-LDH(Arg) and MgFe(Arg)-LDH coating samples are 5.16×10 (-8) , 1.14×10 (-7) , 2.85×10 (-7) and 1.37×10 (-6) A.cm -2 The smaller the corrosion current density of the sample, the slower the corrosion of the sample and the stronger the corrosion resistance. Therefore, the amino acid ion intercalated LDH coating prepared by the present invention enhances the corrosion resistance of the magnesium alloy.
[0032] 3. After the coating prepared by the method of the present invention is corroded, the products are mainly Mg, Fe and amino acids. 2+It can participate in human metabolism, promote osteogenic differentiation, and maintain human health. The Fe element can participate in the synthesis of hemoglobin in the human body, maintain immune function, participate in the transport of oxygen, and amino acids can participate in the synthesis of proteins. Therefore, the amino acid intercalated MgFe-LDH coating prepared by the present invention has good biocompatibility and is conducive to bone repair. 4. Description of the drawings:
[0033] Figure 1 Morphological images of PEO, FeOOH, MgFe-LDH(Tyr), MgFe(Tyr)-LDH and MgFe(Arg)-LDH coatings prepared by the present invention;
[0034] Depend on Figure 1 It can be seen that the PEO coating presents a worm-like porous structure, the FeOOH coating forms irregular nanosheets, and the LDH coating forms hexagonal nanosheets;
[0035] Figure 2 FTIR and XRD patterns of PEO, FeOOH, Fe-Tyr, MgFe-LDH(Tyr) and MgFe(Tyr)-LDH coatings prepared by the present invention;
[0036] It can be seen from the XRD graph that the diffraction peaks at 11° to 15° in the MgFe-LDH(Tyr) and MgFe(Tyr)-LDH coatings correspond to the diffraction characteristic peaks detected for the LDH phase; and it can be seen from the FITR graph that the functional groups of tyrosine are detected in the MgFe-LDH(Tyr) and MgFe(Tyr)-LDH coatings;
[0037] Figure 3 Electrochemical test results of PEO, MgFe-LDH, MgFe-LDH(Tyr), MgFe(Tyr)-LDH, MgFe-LDH(Arg), and MgFe(Arg)-LDH coatings prepared by the present invention;
[0038] exist Figure 3 In the figure, the Tafel curve and impedance spectrum show that the corrosion resistance of the LDH coating intercalated with amino acid ions is enhanced;
[0039] Figure 4 Morphological diagram of MC3T3-E1 mouse osteoblasts cultured on PEO, FeOOH, Fe-Tyr, MgFe-LDH(Tyr) and MgFe(Tyr)-LDH coatings prepared by the present invention for 24 h;
[0040] Depend on Figure 4It can be seen that the FeOOH, Fe-Tyr, MgFe-LDH(Tyr), and MgFe(Tyr)-LDH coatings are beneficial for cell adhesion and spreading;
[0041] Figure 5 Proliferation of MC3T3-E1 mouse osteoblasts in sample culture;
[0042] Depend on Figure 5 It can be seen that MgFe-LDH(Tyr) and MgFe(Tyr)-LDH coatings are beneficial to cell growth. V. Specific implementation methods:
[0043] The present invention is further described below in conjunction with the embodiments, but the scope of protection of the technical solution of the present invention is not limited. The following embodiments are only preferred embodiments of the present invention.
[0044] Embodiment 1:
[0045] The preparation method of the amino acid ion intercalated MgFe-LDH (Tyr) composite coating of the present invention comprises the following detailed steps:
[0046] 1) Prepare a ZE21C magnesium alloy with a diameter of 10 mm as a substrate, and cut it into a thin sheet with a thickness of 2.5 mm; then use 400 mesh water-abrasive paper, 800 mesh water-abrasive paper and 1000 mesh water-abrasive paper to polish the front, back and side surfaces of the magnesium alloy substrate thin sheet in turn; place the polished magnesium alloy substrate in anhydrous ethanol for ultrasonic cleaning for 5 minutes; after cleaning, take out the sample and put it back into anhydrous ethanol for standby use (by pre-treating the magnesium alloy substrate, the oxide film and impurities on the surface of the magnesium alloy can be removed to prepare a better coating);
[0047] 2) Plasma electrolytic oxidation of PEO is performed on the pretreated magnesium alloy substrate to obtain a PEO sample, and the obtained PEO sample is placed in anhydrous ethanol for standby use;
[0048] The specific process of the plasma electrolytic oxidation is as follows: first, 40g of potassium hydroxide and 50g of sodium glycerophosphate are dissolved in deionized water to prepare a 4L mixed solution, and the obtained mixed solution is used as an electrolyte and is placed in a graphite electrode; a constant voltage method is used to adjust the frequency of the high-frequency pulse power supply to 1000Hz, the duty cycle to 10%, the voltage to 320V, and the boost time to 10s; the sample obtained in step 2) is placed in the mixed solution, connected to the positive electrode of the power supply, the graphite electrode is connected to the negative electrode of the power supply, and the instrument is turned on for plasma electrolytic oxidation, and the timing is 130s (the purpose of plasma electrolytic oxidation is to form a dense and porous MgO ceramic coating on the surface of the magnesium alloy, which can better perform chemical deposition to form the coating);
[0049] 3) 100 mg of FeCl 2 ·4H2 O is dissolved in deionized water to prepare 50mL solution A; 25mL solution A is placed in a glass dish, and then 8-15 pieces of PEO samples obtained in step 2) are placed, and then the glass dish is placed on a shaker at room temperature for shaking treatment, and the speed of the shaker is controlled to be 60rpm and the shaking time is 30min; after 30min, the solution is poured out, and the remaining solution A is added and shaken for 90min under the same speed condition;
[0050] 4) placing the sample obtained after the treatment in step 3) in anhydrous ethanol for ultrasonic washing for 5 minutes, placing it in an oven after washing, and drying it at 50° C. for 12 hours; taking it out, adding anhydrous ethanol for ultrasonic washing, and then placing it in an oven again for drying at 50° C. for 12 hours;
[0051] 5) Prepare 15 mL of 5 mmol / L NaOH solution, so that the pH of the NaOH solution is 10, and then add 10 mg of tyrosine (Tyr);
[0052] 6) placing the dried sample in step 4) and the solution prepared in step 5) in a polytetrafluoroethylene autoclave for heating at a temperature of 120° C. for 6 h;
[0053] 7) The sample after the heat treatment in step 6) was ultrasonically cleaned with anhydrous ethanol, and then placed in an oven for drying (drying temperature of 50° C., drying time of 12 h), to obtain an amino acid ion intercalated MgFe-LDH (Tyr) composite coating.
[0054] Embodiment 2:
[0055] The preparation method of the amino acid ion intercalated MgFe(Tyr)-LDH composite coating of the present invention is basically the same as that of Example 1, except that:
[0056] Step 3): 10 mg of tyrosine and 100 mg of FeCl 2 ·4H 2 O was dissolved in deionized water to prepare 50 mL of solution A;
[0057] In step 5), 15 mL of 5 mmol / L NaOH solution and 60 mL of deionized water were prepared and mixed;
[0058] In step 7), after drying, an amino acid ion-intercalated MgFe(Tyr)-LDH composite coating is obtained.
[0059] Embodiment 3:
[0060] The preparation method of the amino acid ion intercalated MgFe-LDH (Arg) composite coating of the present invention is basically the same as that of Example 1, except that:
[0061] In step 5), 15 mL of 5 mmol / L NaOH solution was prepared to a pH of 10, and then 10 mg of arginine (Arg) was added;
[0062] In step 7), after drying, an amino acid ion intercalated MgFe-LDH (Arg) composite coating is obtained.
[0063] Embodiment 4:
[0064] The preparation method of the amino acid ion intercalated MgFe(Arg)-LDH composite coating of the present invention is basically the same as that of Example 1, except that:
[0065] Step 3): 10 mg of arginine and 100 mg of FeCl 2 ·4H 2 O was dissolved in deionized water to prepare 50 mL of solution A;
[0066] In step 5), 15 mL of 5 mmol / L NaOH solution and 60 mL of deionized water were prepared and mixed;
[0067] In step 7), after drying, an amino acid ion-intercalated MgFe(Arg)-LDH composite coating is obtained.
[0068] In addition to the above amino acids, other amino acids such as phenylalanine (Phe), serine (Ser), tryptophan (Try), glutamic acid (Glu) and other amino acids can be used to construct the MgFe-LDH coating.
[0069] The surface morphology of the samples was observed by scanning electron microscopy. Figure 1 As shown, (a) shows the uniform and dense pores on the surface of the PEO sample, and (b) shows the FeOOH coating covering the pores generated on the surface of the PEO coating. From (c), (d) and (e), it can be seen that the MgFe-LDH(Tyr), MgFe(Tyr)-LDH and MgFe(Arg)-LDH composite coatings grow uniformly and densely on the surface of the magnesium alloy. From (c-2), (d-2) and (e-2), it can be seen that a dense and uniform nanosheet structure is generated on the surface of the magnesium alloy. The nanosheets of the MgFe-LDH(Tyr), MgFe(Tyr)-LDH and MgFe(Arg)-LDH composite coatings grow vertically on the surface of the magnesium alloy.
[0070] The samples were analyzed for phase and chemical composition by X-ray diffractometer and Fourier transform infrared spectrometer. The analysis results are shown in the attached Figure 2 .from Figure 2 As can be seen in (a), LDH crystalline phase was detected in MgFe-LDH(Tyr) and MgFe(Tyr)-LDH composite coatings, indicating that LDH coatings were prepared on the surface of magnesium alloys. Mg comes from the magnesium matrix, MgO comes from the MgO ceramic coating formed by plasma electrolytic oxidation, FeOOH is produced by chemical deposition, and LDH is produced by hydrothermal treatment; Figure 2 (b) shows the functional group composition of the sample surface. Figure 2 (b) It can be found that tyrosine functional groups were detected in the coatings of MgFe-LDH(Tyr) and MgFe(Tyr)-LDH samples, which indicates that the amino acid was successfully inserted into the coating.
[0071] The corrosion resistance of the samples was tested by electrochemical experiments. The test results are detailed in the attached Figure 3 . By attaching Figure 3 The Tafel curve, impedance spectrum and Table 1 are used to judge the corrosion resistance of the samples. Figure 3 (a) is the Tafel diagram of the sample, which shows the corrosion potential and corrosion current density of the sample. The corrosion potential indicates the potential at which the sample starts to corrode, and the corrosion current density indicates the corrosion rate of the sample. Therefore, the larger the corrosion potential, the smaller the corrosion current density, and the stronger the corrosion resistance of the sample. The data in Table 1 are the corrosion potential and corrosion current density of the sample. Figure 3 (a) and Table 1 comprehensively analyze the corrosion current density and corrosion potential of each sample. It can be concluded that the coating prepared by the present invention enhances the corrosion resistance of the magnesium alloy. The corrosion resistance of MgFe(Tyr)-LDH and MgFe-LDH(Tyr) coatings is the best, and the corrosion resistance of MgFe-LDH(Arg) is second. Figure 3 (b) shows the impedance spectrum of the sample, which indicates the impedance of the sample. The larger the impedance, the better the corrosion resistance of the sample. As can be seen from the figure, the impedance of the MgFe(Tyr)-LDH and MgFe-LDH(Tyr) coatings is the largest and the corrosion resistance is the best. Comprehensive analysis shows that the amino acid ion intercalated LDH coating prepared by the present invention enhances the corrosion resistance of the magnesium alloy.
[0072] Table 1 Corrosion voltage (E corr ) and corrosion current density (I corr )
[0073]
[0074] Attached Figure 4 and attached Figure 5 The cell morphology images of MC3T3-E1 cells cultured on different samples for 24 h and the proliferation images after 5 days of culture are shown respectively. Figure 4The adhesion and spreading of cells in the sample are shown. Figure 4 It can be found that the cells spread in a spherical shape on the PEO sample and the number is small, while the number of cells on the FeOOH, MgFe-LDH(Tyr) and MgFe(Tyr)-LDH samples increases, and pseudopodia are shown, and the cell spreading area increases; Figure 5 It can be concluded that compared with other samples, the number of cells on MgFe-LDH(Tyr) and MgFe(Tyr)-LDH samples is the largest and the cell adhesion state is the best. Figure 5 The analysis of the absorbance of different samples showed that after the cells were cultured on the samples for 5 days, the number of cell proliferation on the PEO, FeOOH, MgFe-LDH, MgFe(Tyr)-LDH and MgFe-LDH(Tyr) samples increased in turn, indicating that the amino acid intercalated MgFe-LDH coating prepared by the present invention is beneficial to cell proliferation.
[0075] In summary, the preparation method of the amino acid intercalated MgFe-LDH composite coating of the present invention is simple, convenient, easy to operate, environmentally friendly and low in cost. The coating prepared by the method is dense and has uniform thickness. Both composite coatings grow uniformly and densely on the magnesium alloy substrate. They present a nanosheet structure that grows vertically on the surface of the magnesium alloy. The loaded amino acid makes it have a very strong ability to replace negative ions in the corrosive solution (such as Cl - ), thereby enhancing the corrosion resistance of magnesium alloys. The two MgFe-LDH composite coatings grown on the surface of magnesium alloys have good biocompatibility and are conducive to cell growth.
[0076] In the above description, many specific details are described in order to fully understand the technical solution of the present invention. However, the above description is only a preferred embodiment of the present invention, and the present invention can be implemented in many other ways different from those described herein. Therefore, the present invention is not limited to the specific implementation disclosed above. At the same time, any person familiar with the technical field can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the protection scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention, which does not depart from the protection scope of the technical solution of the present invention, still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing an amino acid ion intercalated MgFe-LDHs composite coating, characterized in that: The preparation method comprises the following steps: 1) preparing a magnesium alloy matrix, and then pretreating the magnesium alloy matrix; 2) Plasma electrolytic oxidation of PEO is performed on the pretreated magnesium alloy substrate to obtain a PEO sample, and the obtained PEO sample is placed in anhydrous ethanol for standby use; 3) dissolving FeCl2·4H2O, or amino acid and FeCl2·4H2O in deionized water to prepare solution A; placing the obtained solution A in a container, and then placing the PEO sample obtained in step 2), and then placing the container on a shaker at room temperature for shaking treatment; 4) placing the sample obtained after the treatment in step 3) in anhydrous ethanol for ultrasonic washing, and then drying it in an oven; 5) preparing a NaOH solution so that the pH of the NaOH solution is 9 to 11, and then adding amino acids; Alternatively, a NaOH solution is prepared so that the pH of the NaOH solution is 9 to 11; 6) placing the sample dried in step 4) and the solution prepared in step 5) in a polytetrafluoroethylene autoclave for heating treatment; 7) The sample after the heat treatment in step 6) is ultrasonically cleaned with anhydrous ethanol, and then placed in an oven for drying to obtain an amino acid ion intercalated MgFe-LDHs composite coating.
2. The method for preparing the amino acid ion intercalated MgFe-LDHs composite coating according to claim 1, characterized in that: The magnesium alloy substrate in step 1) is a magnesium alloy rod with a diameter of 10 mm; when used, the magnesium alloy rod is cut into thin sheets with a thickness of 1 to 3.5 mm.
3. The method for preparing the amino acid ion intercalated MgFe-LDHs composite coating according to claim 1, characterized in that: The specific process of pretreating the magnesium alloy substrate in step 1) is as follows: Firstly, the front, back and sides of the magnesium alloy substrate were polished in turn with 400-mesh water-abrasive paper, 800-mesh water-abrasive paper and 1000-mesh water-abrasive paper; the polished magnesium alloy substrate was placed in anhydrous ethanol for ultrasonic cleaning; after cleaning, the sample was taken out and placed in anhydrous ethanol again for standby use.
4. The method for preparing the amino acid ion intercalated MgFe-LDHs composite coating according to claim 1, characterized in that: The specific process of plasma electrolytic oxidation in step 2) is: First, potassium hydroxide and sodium glycerophosphate are dissolved in deionized water to prepare a mixed solution, and the obtained mixed solution is used as an electrolyte and is placed in a graphite electrode; a constant voltage method is used to adjust the frequency of a high-frequency pulse power supply to 900-1200 Hz, a duty cycle to 10%, a voltage to 300-380 V, and a boost time to 3-15 s; a fixed sample obtained in step 2) is placed in the mixed solution, connected to the positive electrode of the power supply, the graphite electrode is connected to the negative electrode of the power supply, and the instrument is turned on for plasma electrolytic oxidation, and the timing is 2-5 minutes.
5. The method for preparing the amino acid ion intercalated MgFe-LDHs composite coating according to claim 4, characterized in that: The addition ratio of potassium hydroxide, sodium glycerophosphate and deionized water is 40-50g:30-50g:4L.
6. The method for preparing the amino acid ion intercalated MgFe-LDHs composite coating according to claim 1, characterized in that: Step 3) When dissolving FeCl2·4H2O in deionized water, the mass volume ratio of FeCl2·4H2O and deionized water is 1-5 mg:1 mL; When the amino acid and FeCl2·4H2O are dissolved in deionized water, the ratio of FeCl2·4H2O, amino acid and deionized water added is 1-5 mg: 0.2-1 mg: 1 mL.
7. The method for preparing the amino acid ion intercalated MgFe-LDHs composite coating according to claim 1, characterized in that: During the shaking treatment in step 3), the rotation speed of the shaking table is controlled to be 10-100 rpm and the shaking time is controlled to be 60-120 min.
8. The method for preparing the amino acid ion intercalated MgFe-LDHs composite coating according to claim 1, characterized in that: During the drying in step 4), the drying temperature is controlled to be 40-60° C. and the drying time is controlled to be 12-48 hours.
9. The method for preparing the amino acid ion intercalated MgFe-LDHs composite coating according to claim 1, characterized in that: In step 5), the ratio of the amount of amino acid to the amount of NaOH solution added is 10-100 mg:75 mL.
10. The method for preparing the amino acid ion intercalated MgFe-LDHs composite coating according to claim 1, characterized in that: During the heating treatment in step 6), the temperature is controlled to be 80-150° C. and the heating time is 3-10 hours.
Citation Information
Cited By
Flame-retardant energy storage cable and preparation method thereof
CN119490703A
Ultraviolet aging resistant photovoltaic cable and preparation method thereof
CN119775695A